Characterization of coriander (Coriandrum sativum) genotypes based on floral traits (Current Horticulture, 2024)
An experiment was conducted on 64 genotypes of coriander to characterize them for various morphological characters. On account of days to 50% flowering, [13 genotypes were grouped as early flowering (100 days)]; based on corolla colour, [32 were grouped as white, 25 as pink and 7 as purple], based on visual observation of presence or absence of involucre, all genotypes were categorized into two groups, 59 showed the presence of involucre and only five genotypes were found without involucre. The arrangement of umbellets in umbel [29 were observed as loose umbel, 35 were observed as compact umbel]. While 17 genotype were classified as less umbel (150)]. The 21 genotypes were categorized into less umbellet group (6) group. Two groups were formed based on number of seeds/umbellet, viz. 14 were grouped as less-seeded (6) genotypes. Fourteen genotypes were found low yielder (60 g).
Keywords: Genotypes; Characterization; Involucre; Seed yield